Application of the Video-Assisted Problem Based Learning Model to Increase Student Learning Motivation in Virus Material - Yuli Ananda; Hafnati Rahmatan; Samingan; Ismul Huda; Mudatsir (Postgraduate, University of Mataram, 2023)
Learning activities are strongly empowered by the use of appropriate teaching models and media. If learning activities are not well designed and correct, it will affect learning outcomes. motivation are indicators in improving the quality of education. The problem in virus material is the demand to understand concepts and imagine abstract things. Therefore, it is necessary to apply the video-assisted Problem Based Learning model to virus material. The purpose of this study is to determine the application of the video-assisted Problem Based Learning model to improve student learning outcomes, to determine differences in the application of the video-assisted Problem Based Learning model to student motivation and the relationship between learning outcomes and motivation as a result of applying the Problem Based Learning model at MAN 1 Aceh Besar and MAN 3 Aceh Besar. This research is Quantitative with a Quasi-Experimental approach with a nonrandomized control group design, pretest-posttest design only. The research sample is 121 students, the instruments used in this study are test instruments for learning outcomes and non-test instruments ARCS motivation questionnaire for motivation. The data on students' learning outcomes and motivation is analyzed by using the Independent t-test. The results shows that the value of motivation shows at the level of t (119) = 14.173, p<0.01) which means there is a difference in motivation between control and experimental classes, and there is a positive relationship between learning outcomes and motivation. The conclusion in this study is that the application of the video-assisted Problem Based Learning model has a significant effect on motivation of students in the control class and experimental class.